Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap kepuasan Kerja Karyawan di Koperasi Kredit Hiro Heling - Yuliana Detun; Antonius Philippus Kurniawan; Vinsensius Ama Muda (Jurnal Projemen UNIPA, 2022)
This research was grounded on the issue of employee job satisfaction at the Hiro Heling Credit Cooperative. This research aimed to (1) Know the description of employee job satisfaction, organizational culture, and organizational commitment. (2) analyze the influence of organizational culture and organizational commitment on employee job satisfaction either partially or simultaneously.The population in this study were KSP Kopdit Hiro Heling office employees, totaling 63 people. Due to limited population, this research was conducted through census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods. Hypothesis testing was done through the F-test and t test.The descriptive analysis shows that the variables of employee job satisfaction, organizational culture, and organizational commitment were categorized as good. The results of the t-test statistic revealed that partially, organizational culture and organizational commitment had a significant influence on employee job satisfaction. The results of the F-test statistics show that simultaneously, the two independent variables had a significant influence on employee job satisfaction. The determination analysis shows that the magnitude of the contribution of organizational culture and organizational commitment to employee job satisfaction at the Hiro Heling Credit Cooperative had a 61% impact on employee work satisfaction at the Hiro Heling Credit Cooperative, whereas 39 % were influenced by factors other than the research variables.